THE EFFECT OF SIZE AND OWNERSHIPS STRUCTURE ON CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE IN PUBLISHED ANNUAL REPORT (A Survey on Industries Company Listed in Indonesian Stock Exchange) - Wirmie Eka Putra (InFestasi, 2009)
The purpose of this research was to know and analyze theeffect of size and ownerships structure on corporate socialresponsibility disclosure in published annual report in industries listedin Indonesian Stock Exchange. The selection of sample was done byusing method systematic random sampling. This research took 72companies as research samples. The checklist was used as theresearch instrument supported by documentation of the data which wastaken from Indonesian Capital Market Directory published in 2008 andAnnual Reports year end 31 December 2007. The result of this researchshows that company size, degree of domestic ownerships and degree offoreign ownerships influence corporate social responsibility disclosureas simultaneously although partially.